Medical Multimedia Image Analysis of Scoliosis in Children Aged 3–7 Years Based on Adaptive Multiobjective Differential Evolution Algorithm. (30th September 2021) - Huang, Chunxiang
Abstract : Scoliosis is mainly caused by the spinal column deviating from its centerline during the growth process. It usually occurs in children aged 3–7 years old. After a detailed analysis of the existing scoliosis detection methods, this paper compares and analyzes the advantages of using multimedia image processing technology to check scoliosis in children aged 3–7 years and uses an adaptive multiobjective differential evolution algorithm to perform scoliosis comprehensive testing. Finally, the experimental analysis shows that the adaptive multiobjective differential evolution algorithm is applied to scoliosis detection to analyze the characteristics of children's cervical spine curvature and the relationship between the cervical spine curvature and the scoliosis angle.